Integrative lncRNA landscape reveals lncRNA-coding gene networks in the secondary cell wall biosynthesis pathway of moso bamboo (Phyllostachys edulis) - Wang, Jiongliang; Hou, Yinguang; Wang, Yu; Zhao, Hansheng (BMC genomics, 2021)
Background LncRNAs are extensively involved in plant biological processes. However, the lack of a comprehensive lncRNA landscape in moso bamboo has hindered the molecular study of lncRNAs. Moreover, the role of lncRNAs in secondary cell wall (SCW) biosynthesis of moso bamboo is elusive. Results For comprehensively identifying lncRNA throughout moso bamboo genome, we collected 231 RNA-Seq datasets, 1 Iso-Seq dataset, and 1 full-length cDNA dataset. We used a machine learning approach to improve the pipeline of lncRNA identification and functional annotation based on previous studies and identified 37,009 lncRNAs in moso bamboo. Then, we established a network of potential lncRNA-coding gene for SCW biosynthesis and identified SCW-related lncRNAs. We also proposed that a mechanism exists in bamboo to direct phenylpropanoid intermediates to lignin or flavonoids biosynthesis through the PAL/4CL/C4H genes. In addition, we identified 4 flavonoids and 1 lignin-preferred genes in the PAL/4CL/C4H gene families, which gained implications in molecular breeding. Conclusions We provided a comprehensive landscape of lncRNAs in moso bamboo. Through analyses, we identified SCW-related lncRNAs and improved our understanding of lignin and flavonoids biosynthesis.